Labour supply and labour force participation in Europe: a discussion of some recent developments and projections - Mathieu Plane; Jörg Döpke; Odile Chagny; Rainer Schmidt (Kiel Institute of World Economics (IfW), 2001)
The prospects for labour supply in Europe are considered. The analysis begins with a so-called labour market balance covering the development on an aggregate level. Estimations to shed light on the relation between unemployment and labour force participation are given in the second part of the paper. Detailed analyses of the forces behind the participation rates for individual countries and labour force projections are given. We expect the labour force in Europe to decline during the next years. However, the impact of this development on unemployment is rather limited.
Keywords: C2; J0; J1; 330; Labour Force; Labour Force Participation; Unemployment; Europe; Arbeitsangebot; Erwerbstätigkeit; Arbeitslosigkeit; Erwerbspersonenpotential; Arbeitsmarktprognose; EU-Staaten; Frankreich; Deutschland; Italien; Spanien; Großbritannien; Vereinigte Staaten